As línguas de fronteira. Alguns exemplos das interferências das línguas vizinhas - Mikołajczak, Sylwia (Neophilologica, 2012)
The natural coexistence of languages remaining in the close geographical contact leads to language transfer. The aim of this article is to present some examples of the transfer that involves the influence between Spanish and Portuguese in Olivença, in Portugal, and on the Brazilian-Uruguay border (the cities of Rivera-Livramento). Therefore, it is anticipated that certain features of the interference occurring in the regions mentioned above may be generalized to reveal some facts about the mechanisms of language acquisition. Moreover, the examples we analyzed lead us to the conclusion that certain regular interference patterns can also be found during the Portuguese lessons with the groups of students of the Spanish philology.